Suitability of Sprouted and Fresh Three Potato Cultivars for Chip Manufacture: A Chemical and Sensory Evaluation - Mohammed, Heshw Farhad; Aljabary, Ali Muhi Aldeen Omar (Kurdistan Journal of Applied Research, 2025)
Potatoes are a globally important crop and a key raw material for the production of chips. Sprouting during potato storage is a critical problem that alters chemical and sensory attributes such as sugar accumulation, starch reduction, and firmness loss, which negatively affect chip quality. However, limited studies have addressed these changes across cultivars under local conditions. The present study explored the influence of fresh potato (at harvest) and sprouting stages (non-sprouted, and sprouted at 1 cm and 2 cm length) on the chemical properties and sensory quality of three potato chip cultivars (Crozo, Hermes, and Lady Rosetta), which are widely grown in the Kurdistan Region of Iraq. To ensure clarity of the experimental design, the study specifically evaluated these three cultivars across four developmental stages to assess their chemical and sensory quality for chip production. After that, the results indicated that Crozo exhibited the highest dry matter (29.78%) and starch (22.53%) at 2 cm sprouting, indicating strong frying potential. Lady Rosetta exhibited the least weight loss (5.85%) and the highest firmness (33.02 N) at harvest. TSS increased after storage, peaking in Lady Rosetta (8.67 %), while total sugar content decreased during sprouting to 0.089%. Sensory scores for chips declined with increased sprout length. Crozo and Lady Rosetta maintained a better appearance, flavor, and texture during the sprouting stages than Hermes. Overall, the cultivar and sprouting stages had a significant influence on quality. Fresh and non-sprouted potatoes are recommended for optimal chip quality. The results concluded that Crozo and Lady Rosetta cultivars are most suitable for storage conditions and processing due to their favorable chemical traits and sensory performance.